Effects of single N-glycosylation site knockout on folding and defibrinogenating activities of acutobin recombinants from HEK293T. (February 2015) - Tsai, Inn-Ho; Wang, Ying-Ming; Huang, Kai-Fa
Abstract: Acutobin, the α-fibrinogenase from Deinagkistrodon acutus venom, contains four N-glycosylation sites with disialylated complex-typed glycans. Here, we explore the functional roles of each of the N -glycan by site-directed mutagenesis. The wild-type (ATB-wt) and single glycan-knockout mutants of recombinant acutobin were prepared from HEK293T, demonstrating that mutations at Asn 77, Asn 81 and Asn 100 impaired the folding while the S79A mutant and various Asn 229 -deglycosylated mutants were correctly folded. Based on homology modeling of acutobin and multiple sequence alignment with various venom thrombin-like enzymes, the importance of a hydrophilic environment at each glycosylation site to the enzyme folding could be rationalized. Remarkably, all the mutants showed similar catalytic activities for the chromogenic substrate and similar thermal stabilities as ATB-wt, suggesting that the glycan knockout did not affect the gross conformation and stability of the active sites. Although SDS-PAGE analyses revealed that ATB-wt and the D229-mutant degraded all human fibrinogen subunits faster but less specifically in vitro as compared with other mutants that cleaved only the α-subunit, ATB-wt and D229-mutant were not able to release fibrinogen-peptide A and thus coagulated human plasma slower than the other mutants did. In the mice model, the defibrinogenating effect of ATB-wt was stronger and lasting-longer than those of all the mutants. Taken together, all the glycans contribute to the pharmacokinetics of acutobin and ATB-wt in vivo, and the microenvironment around the Asn 229 -glycan appears to regulate the fibrinogen-chain specificity of acutobin while the N -glycans at positions 77, 81 and 100 are crucial for its folding. Graphical abstract: Highlights: Single glycan knockout at Asn 77, Asn 81 or Asn 100 impaired the folding of recombinant acutobin. The wild-type and the D229 mutant hydrolyzed all the fibrinogen subunits. Structure near the Asn 229 -glycan may regulate the fibrinogen-chain specificity. The mouse in vivo defibrinogenating efficacies: acutobin > recombinant wt >> glycan-knockout mutants.